2008
DOI: 10.1111/j.1466-7657.2008.00656.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional patterns of Korean diabetic patients: an exploratory study

Abstract: This study revealed a significant deviation from recommended daily allowances in the nutritional intake of Korean diabetic patients and emphasizes that dietary teaching and counselling must be tailored to clients' specific cultures and ethnic backgrounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
(33 reference statements)
2
12
0
Order By: Relevance
“…Furthermore, negative correlations between HbA1c levels and protein or fat intake were also observed. In another study using Korean patients with diabetes mellitus, the distribution of macronutrients (%E of protein : %E of fat : %E of carbohydrate) was reported as 16:16:68 16 . The mean %E of carbohydrate was 59.5 in men and 58.6 in women, respectively, in the present study (Table 1).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Furthermore, negative correlations between HbA1c levels and protein or fat intake were also observed. In another study using Korean patients with diabetes mellitus, the distribution of macronutrients (%E of protein : %E of fat : %E of carbohydrate) was reported as 16:16:68 16 . The mean %E of carbohydrate was 59.5 in men and 58.6 in women, respectively, in the present study (Table 1).…”
Section: Discussionsupporting
confidence: 60%
“…In another study using Korean patients with diabetes mellitus, the distribution of macronutrients (%E of protein : %E of fat : %E of carbohydrate) was reported as 16:16:68. 16 The mean %E of carbohydrate was 59.5 in men and 58.6 in women, respectively, in the present study (Table 1). Thus, Korean elderly diabetic patients' intake energy more from carbohydrate than Japanese elderly diabetic patients.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Thus, carbohydrate intake takes up a relatively high proportion of macronutrients in Asian patients with T2DM. In a Korean study, the distribution of macronutrients (C:F:P, % of total energy) was reported as 68%:16%:16%, respectively [29]. According to data from eastern China, in patients with T2DM, the proportion of calories derived from carbohydrate, fat and protein were 61.4%, 25.4% and 13.3%, respectively [30].…”
Section: Literature About the Effects Of High Carbohydrate On Metamentioning
confidence: 99%
“…So far, the current reports of food intake and clinical recommendations are based on studies of Caucasian subjects. Studies on the nutrient intake of Korean diabetic patients have only looked at a small number of patients, such as 154 patients [7], and therefore the overall state of dietary intake of Korean diabetic patients could not be evaluated. For a large scale study, the development of a validated diet assessment method is required and although studies in diabetic patients have been conducted in other populations [8] in Korea, except for a semi-quantitative food frequency questionnaire (FFQ) in a community cohort for the study of chronic diseases [9] and a food intake questionnaire for the investigation of the dietary patterns associated with the development of diabetes [10], there has been no study on the dietary assessment method for diabetic patients exclusively.…”
Section: Introductionmentioning
confidence: 99%